Convergent Real Sequence/Examples/Term is Geometric Mean of Preceding Two Terms

From ProofWiki
Jump to navigation Jump to search

Example of Convergent Real Sequence

Let $a, b \in \R_{>0}$ be (strictly) positive real numbers such that $a \le b$.

Let $a, b \in \R_{>0}$ be such that $a \le p \le q \le b$.

Let $\sequence {x_n}_{n \mathop \in \N_{>0} }$ be the sequence in $\R$ defined as:

$x_n = \begin {cases} p & : n = 1 \\ q & : n = 2 \\ \sqrt{x_{n - 1} x_{n - 2} } & : n > 2 \end {cases}$

That is, beyond the first $2$ terms, each term is the geometric mean of the previous $2$ terms.

Then $\sequence {x_n}$ converges.


Proof

First note that:

$a \le x_m \le b$ for $m \in \set {1, 2}$.

It can be shown by Proof by Mathematical Induction that:

$\forall n \in \N_{>0}: a \le x_n \le b$

Then:

\(\displaystyle a\) \(\le\) \(\displaystyle x_{n + 1}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \dfrac a b\) \(\le\) \(\displaystyle \dfrac {x_{n + 1} } b\)
\(\displaystyle \) \(\le\) \(\displaystyle \dfrac {x_{n + 1} } {x_n}\)


and:

\(\displaystyle x_{n + 1}\) \(\le\) \(\displaystyle b\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \dfrac {x_{n + 1} } a\) \(\le\) \(\displaystyle \dfrac b a\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \dfrac {x_{n + 1} } {x_n}\) \(\le\) \(\displaystyle \dfrac b a\)

That is:

$\dfrac a b \le \dfrac {x_{n + 1} } {x_n} \le \dfrac b a$


Then we have:

\(\displaystyle {x_{n + 2} }^2 - {x_{n + 1} }^2\) \(=\) \(\displaystyle x_{n + 1} x_n - {x_{n + 1} }^2\)
\(\displaystyle \) \(=\) \(\displaystyle x_{n + 1} \paren {x_n - x_{n + 1} }\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x_{n + 2} - x_{n + 1} }\) \(=\) \(\displaystyle \dfrac {x_{n + 1} } {x_{n + 2} + x_{x + 1} } \size {x_n - x_{n - 1} }\)
\(\displaystyle \) \(\le\) \(\displaystyle \dfrac b {a + b} \size {x_n - x_{n - 1} }\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x_{n + 2} - x_{n + 1} }\) \(=\) \(\displaystyle \paren {\dfrac b {a + b} }^{n - 1} \size {x_2 - x_1}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x_n - x_m}\) \(=\) \(\displaystyle \size {\paren {x_n - x_{n - 1} } + \paren {x_{n - 1} - x_{n - 2} } + \dotsb + \paren {x_{m + 1} - x_m} }\)
\(\displaystyle \) \(\le\) \(\displaystyle \size {x_n - x_{n - 1} } + \size {x_{n - 1} - x_{n - 2} } + \dotsb + \size {x_{m + 1} - x_m}\) Triangle Inequality for Real Numbers
\(\displaystyle \) \(\le\) \(\displaystyle \paren {\paren {\dfrac b {a + b} }^{n - 3} + \paren {\dfrac b {a + b} }^{n - 2} + \dotsb + \paren {\dfrac b {a + b} } } \size {x_2 - x_1}\)



Sources